The Effect of Exercise and Giving Beetroot Juice (Beta Vulgaris L) on Athletes of Futsal Academy Stock Development in 2021 - Gylbert GrenWino Sitompu; Albadi Sinulingga; Rahma Dewi (Budapest International Research and Critics University, 2022)
The purpose of this research isTo determine the effect of exercise and administration of beetroot juice (Beta vulgaris L) onmaximal oxygen volume (VO2max) for futsal athletesStock Development Academy in 2021.The research was conducted using experimental methods. The research design used is One Way Anova. InstrumentBlepp Test as a measuring tool in this study has a validity of 0.915 and a reliability coefficient of 0.868.The subject of this research is futsal athleteacademy STOK Binaguna as many as fifteen people.The data collection technique used in this study was to measure VO2 Max at the beginning and end of the study.The data analysis technique in this study used the t test. From the results of the t-test, it can be seen that the t-count is 1.583 in the exercise treatment group and the administration of beetroot juice, the t-count is 1.890 in the exercise-only treatment group, and the t-count is 2.690 in the treatment group with beet juice only, and t- table for df = 6-2 = 4 which is 2.776. Based on the results of the ANOVA test analysis above, the calculated F value is 0.222 with a significance of 0.804 > 0.05. It was concluded thatexercise and administration of beetroot juice (Beta vulgaris L) had no significant effect on increasingmaximal oxygen volume (VO2max) for futsal athletesAcademy STOK Binaguna 2021.